Comparison of Print Modules and E-Modules to the Tolerance Character of Students - Syahrial, Syahrial; Asrial, Asrial; Kurniawan, Dwi Agus; Damayanti, Latipia (International Journal of Elementary Education, 2021)
Nowadays, the character of tolerance in elementary school students is experiencing degradation. Whereas the character of tolerance is one of the important characters possessed by students in their social life. This study aims to analyze the comparison of responses and tolerance characteristics of students who learn to use two different learning modules, namely the electronic module and the printed module. This research is quantitative descriptive. The population in this study amounted to 243 students. Determination of the sample is done by using the purposive sampling technique, to obtain a sample of 32 students. Data collection in this study used instruments in the form of student response questionnaires and tolerance character questionnaires. The instrument used has been tested for validity and reliability. The collected data were then analyzed using descriptive and inferential statistics, assumption tests (normality and homogeneity), and hypothesis testing (t-test). The results showed that students' responses were more dominant when using the electronic module based on local wisdom than the printed module. The tolerance character that appears is also more visible when using an electronic module based on the local wisdom instead of a printed module. Based on these findings, it was concluded that students' responses when using the electronic module were better than using the print module. Students' tolerance character can also be seen in the application of electronic modules and print modules. So it is recommended that the electronic module based on local wisdom be used as additional teaching materials in learning in elementary schools.